Violence in contemporary society - Ianni, Octavio (FCL-UNESP Laboratório Editorial, 2007)
Some considerations about the many dimensions of modern society, or what we could call modernity, that is able to build forms, techniques and practices of a more and more brutal violence, from the most simple to the most sophisticated, up to the point that we could be able to identify a real industry of violence.